1982
DOI: 10.1139/y82-155
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor has a direct, prostaglandin-independent action on kidneys

Abstract: Intravenous injection of a saline extract of lyophilized rat atrial myocardium into anesthetized rats caused a massive diuresis and natriuresis of short duration. There was also a significant increase in potassium excretion and a fall in urine osmolality. There were no significant changes in solute-free water reabsorption, glomerular filtration rate, renal plasma flow, or filtration fraction as measured by conventional clearance methods. Mean arterial pressure was significantly reduced during the natriuretic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 0 publications
4
34
1
Order By: Relevance
“…Since no correlations could be found between the urinary excretion of any PG and the natriuresis, it appears unlikely that renal PGs are involved in the natriuretic effect of ANP. This finding confirms the results obtained in humans (Miyamori et al, 1987) and animals (Keeler, 1982;Salazar et al, 1988) demonstrating that pharmacological blockade of PG biosynthesis by cyclo-oxygenase inhibition fails to attenuate the natriuresis elicited by ANP infusion. In contrast to natriuresis, the ANP-induced diuresis might rely partly upon the stimulation of renal PG biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since no correlations could be found between the urinary excretion of any PG and the natriuresis, it appears unlikely that renal PGs are involved in the natriuretic effect of ANP. This finding confirms the results obtained in humans (Miyamori et al, 1987) and animals (Keeler, 1982;Salazar et al, 1988) demonstrating that pharmacological blockade of PG biosynthesis by cyclo-oxygenase inhibition fails to attenuate the natriuresis elicited by ANP infusion. In contrast to natriuresis, the ANP-induced diuresis might rely partly upon the stimulation of renal PG biosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, among the four PGs studied, only the two most effective upon the water excretion were found closely related to the UFR. Although the mechanism underlying their possible contribution remains unclear, this would confirm findings by Keeler (1982) who reported that inhibition of the PG biosynthesis attenuated the ANP induced diuresis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding suggests that the increase in prostaglandin excretion seen with the infusion of ANF under control conditions is not mediating the natriuresis. Keeler 17 also has shown that the natriuretic effect of ANF is not prostaglandin-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…The natriuretic effect of atrial extracts is now well documented (DeBold et al, 1981;Keeler, 1982;Trippodo et al, 1983). Furthermore, the factor producing the natriuretic effect ('atrial natriuretic factor' (ANF), a peptide containing an active portion of about 26 amino acid groups) has now been synthesized Thibault et al, 1984;Kangawa & Matsuo, 1984;Seidman et al, 1984).…”
Section: Introductionmentioning
confidence: 99%